A phase III, multicenter, double-blind, randomized clinical trial to evaluate the efficacy and safety of ceftolozane/tazobactam plus metronidazole versus meropenem in Chinese participants with complicated intra-abdominal infections. (October 2022) - Sun, Yihong; Fan, Jia; Chen, Gang; Chen, Xiaofei; Du, Xiaoling; Wang, Ye; Wang, Hui; Sun, Fang; Johnson, Matthew G.; Bensaci, Mekki; Huntington, Jennifer A.; Bruno, Christopher J.
HIGHLIGHTS: Phase III study of ceftolozane/tazobactam (C/T) plus metronidazole for complicated intra-abdominal infection in China. C/T plus metronidazole was noninferior to meropenem for clinical response. Safety was comparable between C/T plus metronidazole and meropenem groups. C/T plus metronidazole had efficacy against extended-spectrum β-lactamase-positive Enterobacterales. ABSTRACT: Objectives: This study aimed to evaluate the efficacy and safety of ceftolozane/tazobactam (C/T) plus metronidazole versus meropenem plus placebo for the treatment of complicated intra-abdominal infection (cIAI) in Chinese adult participants. Methods: In this phase III clinical trial (NCT03830333), Chinese adult participants with cIAI were randomized 1:1 to receive C/T plus metronidazole or meropenem plus placebo. The primary objective was to assess C/T plus metronidazole for noninferiority versus meropenem for clinical response rate at the test of cure (TOC; 28 ± 2 days after study start) visit in the clinically evaluable population. Secondary endpoints included clinical and microbiologic responses at the TOC and end-of-treatment (≤24 hours after last dose) visits and adverse event rates. Results: Clinical cure at the TOC visit in the clinically evaluable population was 95.2% and 93.1% for C/T plus metronidazole and meropenem, respectively (between-treatment difference: 2.1% [95% confidence interval: -4.7%, 8.8%]); thus, noninferiority was met. Clinical responses at the TOC and end-of-treatment visits and microbiologic responses at the TOC visit were consistent with the primary efficacy endpoint. Safety was comparable between study treatment groups. Conclusion: In Chinese adult participants with cIAI, C/T plus metronidazole was noninferior to meropenem, with comparable safety.